Liquefied biomethane for heavy-duty transport in Italy: A well-to-wheels approach. (June 2022) - Tratzi, Patrizio; Torre, Marco; Paolini, Valerio; Tomassetti, Laura; Montiroli, Cassandra; Manzo, Eros; Petracchini, Francesco
Abstract: While environmental benefits of biofuels in general are well known, the impact of liquefaction and carbon capture to the biomethane production chains are yet to be explored. Hence, a well-to-wheels (WtW) analysis of liquified biomethane (bio-LNG, or LBM) production chains was performed; Italy was chosen as case study, having more than 25% of EU methane refuelling stations. Despite increased emissions from the liquefaction process, LBM reaches a negative impact of −572 gCO2eq /km, as it addresses transport emissions and agricultural waste management at the same time. Nitrous oxides (NOx) emissions for biomethane and fossil fuels are mostly similar, as fuel combustion in the vehicle engine is a predominant source of NOx emissions compared to fuel production. The most intensive processes contributing to climate change were biomethane upgrading and liquefaction. Small-scale CO2 capture can provide additional GHG emissions reductions by 7.55 gCO2eq /MJ although this process is also more NOx-intensive compared to other production steps.